2021
DOI: 10.1371/journal.pone.0248781
|View full text |Cite
|
Sign up to set email alerts
|

Structure of human ORP3 ORD reveals conservation of a key function and ligand specificity in OSBP-related proteins

Abstract: Human ORP3 belongs to the oxysterol-binding protein (OSBP) family of lipid transfer proteins and is involved in lipid trafficking and cell signaling. ORP3 localizes to the ER-PM interfaces and is implicated in lipid transport and focal adhesion dynamics. Here, we report the 2.6–2.7 Å structures of the ORD (OSBP-related domain) of human ORP3 in apo-form and in complex with phosphatidylinositol 4-phosphate. The ORP3 ORD displays a helix grip β-barrel fold with a deep hydrophobic pocket which is conserved in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…2). Of note, the structural analyses of yeast Osh3p and mammalian ORP3 showed that the lipid-binding cavity of these ORDs is too narrow to accommodate sterols [39,44], consistent with the view that phosphoinositide rather than sterol binding is a common denominator of the ORPs.…”
Section: Major Structural Features Of Orpssupporting
confidence: 59%
See 3 more Smart Citations
“…2). Of note, the structural analyses of yeast Osh3p and mammalian ORP3 showed that the lipid-binding cavity of these ORDs is too narrow to accommodate sterols [39,44], consistent with the view that phosphoinositide rather than sterol binding is a common denominator of the ORPs.…”
Section: Major Structural Features Of Orpssupporting
confidence: 59%
“…Since the initial Osh4p structure, high-resolution structures of the ORDs of yeast Osh1p [38], Osh3p [39] and Osh6p [40,41], as well as of mammalian ORP1 (Fig. 2) [42], ORP2 [43], and ORP3 [44] have been reported. These structural analyses have revealed interesting differences in the mode of ligand binding to distinct ORP family members: The PI(4,5)P2 binding mode in ORP1 and -2 differs from that of PI4P in the other ORDs.…”
Section: Major Structural Features Of Orpsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yeast Oxysterol homology (Osh) proteins, mammalian OxySterol Binding Protein (OSBP) and Oxysterol-binding Related Proteins (ORP) proteins form another large LTP protein family ( Kentala et al, 2016 ). At least some 22 crystal structures of LTP domains from Osh or ORP proteins have been tallied so far including Osh1 ( Manik et al, 2017 ), Osh3 ( Tong et al, 2013 ), Osh4 ( Im et al, 2005 ; de Saint-Jean et al, 2011 ), Osh6 ( Maeda et al, 2013 ; Moser von Filseck et al, 2015 ), ORP1, ORP2 ( Wang et al, 2019 ) and ORP3 ( Tong et al, 2021 ) bound to different phosphoinositides and/or cholesterol derivatives; these structures reveal the versatility of this particular LTP fold capable of accommodating different types of ligands (e.g., Osh6 binding PS or PI4P and OSBP binding cholesterol or PI4P). A similar versatility can be described for another large class of LTPs including the PRELI and StART/StARkin domains ( Alpy and Tomasetto, 2014 ) ( Figure 3 ) capable of binding a variety of lipids such as PLs (PA or PS) and sterols or ceramides, respectively.…”
Section: Lipid Transfer Proteins: a Large Functional Group Of Proteins Sampling Many Structural Classesmentioning
confidence: 99%